On Certain Type Fractional Integration of Special Functions via Pathway Operator (Global Journal of Science Frontier Research, 2015)
In this present paper we study product of some special functions via pathway fractional integral operator. Our results are quite general in nature .Some known and new results are also obtain here.
Keywords: Pathway fractional integral operator; M-series; New generalized Mittag-Leffler function